PROGRAM REVITALISASI PASAR DI NAGARI RAO-RAO KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT TAHUN 2018 - Wilza Yuli; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The market revitalization program is a mandate from Indonesian President Joko Widodo to the Indonesian Ministry of Trade. The People's Market Revitalization Program is one form of the Indonesian Ministry of Trade's commitment to improve the competitiveness of the people's market, increase the welfare of traders through increasing turnover, support the smooth logistics and distribution of materials needed by the community and encourage the strengthening of domestic markets in an era of global competition that is increasingly wide open . Nagari Rao-Rao Market is one of the Nagari markets in Tanah Datar District which received assistance from the Special Allocation Fund in the assignment of market development for the 2018 fiscal year.This study aims to describe the market revitalization program in Nagari Rao-Rao Sungai Tarab District, Tanah Datar District, West Sumatra Province in 2018. This study uses a qualitative approach. The research location was Nagari Rao-Rao Market, Sungai Tarab District, Tanah Datar District, West Sumatra Province. Data sources in this study are informants and documents. Data collection techniques are done by documentation and interviews. While the data analysis technique is done by qualitative analysis of a descriptive type.The results of this study indicate that there are 3 stages of revitalization, namely physical intervention, economic rehabilitation, and social/institutional revitalization. Physical intervention which is a stage which includes physical repair of Nagari Rao-Rao market building which used to not have complete facilities after being revitalized now has quite complete facilities. Furthermore, economic rehabilitation, after the Nagari Rao-Rao market was carried out revitalization was able to improve the economy of the community and could increase Nagari's income. And the social/institutional revitalization of the election of market leaders is carried out directly through Nagari deliberations. Factors influencing the market revitalization program are, market revitalization budget, communication and human resources.Keywords: Program, Revitalization and Nagari Market.